Safety Profile of Immunotherapy Combined With Antiangiogenic Therapy in Patients With Melanoma: Analysis of Three Clinical Studies - Tian, Hui; Wang, Xuan; Lian, Bin; Yan, Xieqiao; Si, Lu; Chi, Zhihong; Sheng, Xinan; Kong, Yan; Mao, Lili; Bai, Xue; Tang, Bixia; Li, Siming; et al. (Frontiers in Pharmacology, 2021)
Objective To describe the frequency and spectrum of treatment-related aderves events(TRAE) of melanoma patients with immunetherapy combined with antiangiogenic therapy and to evalute the occurrence of AEs associated with progression-free survival and treatment response. Methods This retrospective cohort study included 3 clinical trails with patients of stage III/IVmelanoma who treated with anti–PD 1 combined with antiangiogenic therapy. Results A total of 72 patients were included. The median follow-up time was 25.9months(95%CI 9.1-42.7m). The median treatment duration was 7.5months(range 0.7- 42.8m), and the median treatment circles were 11.0(range 1-90). 70 of 72(97.2%) of patients experienced any grade TRAE. Most of aderves events(AEs) were grade1 or 2. No drug-related deaths were reported. Most TRAEs were observed in heptic(75%), endorcin(72.2%), skin(65.3%), gastrointestinal tract(59.7%), myelosuppression(55.6%), renal(55.6%) and dyslipidemia(54.2%). AEs spectrum was similar between regimens. Using multivariate Cox proportional risk models showed hypertension was an independent risk factor for PFS. Carried by multivariable logistic regression models, ORR was no significantly better based on organs involved. There was a significant superior association between the number organs involved and PFS(P=0.0014), utilizing 5 as the optimal cut-point. Conclusion We found all almost patients experienced TRAEs, most of the TRAEs were slight. The prevalence of AEs were higher than monotherapy. The type of AEs is similar to monotherapy, with no unexpected AEs.